Fracture Toughness Characterization of Lithiated Germanium as an Anode Material for Lithium-Ion Batteries. Issue 2 (1st January 2016) - Wang, Xueju; Yang, Avery; Xia, Shuman
Abstract : Germanium (Ge) is a promising candidate anode material for next-generation, high-performance lithium-ion batteries. Despite its apparent promise, the mechanical properties of lithiated Ge including its fracture characteristic are largely unknown. In this paper, we report the first experimental measurement of the fracture toughness of lithiated Ge using an in-house developed nanoindentation system. The fracture toughness of lithiated Ge is found to increase monotonically with increasing lithium content, indicating a brittle-to-ductile transition of lithiated Ge as lithiation proceeds. We also compare the fracture energy of lithiated Ge with that of lithiated Si and show that, despite a slightly lower fracture energy of Ge than that of Si in the unlithiated state, Ge possesses much higher fracture resistance than Si in the lithiated state. These findings suggest that Ge anodes are intrinsically more resistant to fracture than their Si counterparts, thereby offering substantial potential for the development of durable, high-capacity, and high-rate lithium-ion batteries. The quantitative results from this work provide fundamental insights for developing new electrode materials and help to enable predictive modeling of high-performance lithium-ion batteries.